NtrBC and Nac Contribute to Efficient Shigella flexneri Intracellular Replication - Waddell, Chelsea D. (American Society for Microbiology, 2014)
Shigella flexneri two-component regulatory systems (TCRS) are responsible for sensing changes in environmental conditions and regulating gene expression accordingly. We examined 12 TCRS that were previously uncharacterized for potential roles in S. flexneri growth within the eukaryotic intracellular environment. We demonstrate that the TCRS EvgSA, NtrBC, and RstBA systems are required for wild-type plaque formation in cultured epithelial cells. The phenotype of the NtrBC mutant depended in part on the Nac transcriptional regulator. Microarray analysis was performed to identify S. flexneri genes differentially regulated by the NtrBC system or Nac in the intracellular environment. This study contributes to our understanding of the transcriptional regulation necessary for Shigella to effectively adapt to the mammalian host cell.